2017
DOI: 10.1111/iju.13471
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and limitations of animal models in partial bladder outlet obstruction for translational research

Abstract: Abbreviations & Acronyms AMPA = a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid BOO = bladder outlet obstruction BPH = benign prostatic hyperplasia DO = detrusor overactivity HIF-1 = hypoxia-inducible factor-1 IL = interleukin LUTS = lower urinary tract symptoms NGF = nerve growth factor NO = nitric oxide NVC = non-voiding contraction OAB = overactive bladder pBOO = partial bladder outlet obstruction TGF-b = transforming growth factor-b Abstract: The functions of the lower urinary tract have been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 126 publications
2
28
0
2
Order By: Relevance
“…obstructed bladder dysfunction secondary to BPH is a slow and progressive disease (6). ideally, an accurate model of BPH-induced Boo would develop as gradually as possible (15). In the present study, a significant difference in the pathology between the dBoo group and the GBoo group was observed, which provided evidence that GBoo may serve as a more appropriate model for studying Boo.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…obstructed bladder dysfunction secondary to BPH is a slow and progressive disease (6). ideally, an accurate model of BPH-induced Boo would develop as gradually as possible (15). In the present study, a significant difference in the pathology between the dBoo group and the GBoo group was observed, which provided evidence that GBoo may serve as a more appropriate model for studying Boo.…”
Section: Discussionsupporting
confidence: 56%
“…Pressure stimulation of BMScs during Boo is different compared with normal conditions. The majority of Boos involve chronic and progressive pathological processes; however, previous findings have commonly used acute obstruction models that do not accurately mimic the natural course of Boo (15). a number of studies have reported that the mortality rate of BOO is usually ≥15% (16,17), even when a highly standardized method of obstruction, such as surgery, is applied to induce Boo (18).…”
Section: Urethral Meatus Stricture Boo Stimulates Bladder Smooth Muscmentioning
confidence: 99%
“…As a result, it is widely recognized that surrogate markers need to be used during these situations. Thus, this is the reason why most experimental models are used as non-voiding bladder contractions for OAB symptoms in animals [ 10 ].…”
Section: Luts and Animal Modelsmentioning
confidence: 99%
“…Several animal models have been used to evaluate bladder outlet obstruction in rats [4]. Some of these involve the mechanically induced partial occlusion of the urethra in rats to simulate similar conditions as those observed in patients with prostate-induced urethral obstructions [5]. Despite the efforts made to evaluate the impact of aging on micturition, the reported results have varied greatly, which may be explained by differences in species, sex, the application of anesthetics, and the experimental procedures used [6].…”
Section: Introductionmentioning
confidence: 99%